Geometrically Precise Building Blocks: the Self-Assembly of β-Peptides. Issue 11 (19th November 2015) - Gopalan, Romila D.; Del Borgo, Mark P.; Mechler, Adam I.; Perlmutter, Patrick; Aguilar, Marie-Isabel
Summary: Peptides comprised entirely of β-amino acids, or β-peptides, have attracted substantial interest over the past 25 years due to their unique structural and chemical characteristics. β-Peptides form well-defined secondary structures that exhibit different geometries compared with their α-peptide counterparts, giving rise to their foldamer classification. β-Peptide foldamers can be functionalized easily and are metabolically stable and, together with the predictable side-chain topography, have led to the design of a growing number of bioactive β-peptides with a range of biological targets. The strategic engineering of chemical and topographic properties has also led to the design of β-peptide mimics of higher-order oligomers. More recently, the ability of these peptides to self-assemble into complex structures of controlled geometries has been exploited in materials applications. The focus of this mini-review is on how the unique structural features of β-peptide assemblies have been exploited in the design of self-assembled proteomimetic bundles and nanomaterials. Highlights: β-Peptide foldamers are metabolically stable and geometrically defined Self-assembly of these monomers leads to proteomimetic bundles Supramolecular self-assembly of these peptides creates a variety of nanomaterials Abstract : Peptides comprised entirely of β-amino acids form unique structures that self-assemble to form ion channels, proteomimetic bundles, and DNA mimics. This structural template also allows the tailored design of new nanomaterials with unique physical properties for application in nanotechnology and biomedicine.